Conformational Regulation of Substituted Azepanes through Mono‐, Di‐, and Trifluorination. Issue 12 (27th February 2014) - Patel, Alpesh Ramanlal; Hunter, Luke; Bhadbhade, Mohan M.; Liu, Fei
Abstract: Substituted azepanes have flexible ring structures and this conformational diversity is important for their bioactivity. We have shown that a single fluorine atom, when installed diastereoselectively on a model azepane ring, can bias its ring to one major conformation. Here the conformational effects of mono‐, di‐, and trifluorination, as well as hydroxylation, on substituted azepanes have been investigated by 1 H NMR spectroscopy and computational modeling in chloroform. Fluorine substitution was found to be more effective than hydroxyl group substitution in reducing conformational disorder; however, multiple fluorinations may not lead to additive conformational control and can result in complex conformational outcomes. Abstract : Seven‐membered nitrogen heterocycles have flexible ring structures and this conformational diversity is important for their bioactivity. Here the conformational effects of fluorination, as well as hydroxylation, on an azepane model system are investigated by 1 H NMR spectroscopy and computational modeling.